Management of Putri Al-Aziziyah Kapek Gunungsari Islamic Boarding School Review from Planning Aspects - Sri Amiati; Hari Witono; Asrin Asrin (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2022)
This study aims to determine the management of the female Islamic boarding school Al-Aziziyah Kapek Gunungsari in terms of planning aspects. The approach in this study uses a qualitative approach with a case study method. Data collection techniques were carried out through observation, interviews, and documentation. The research subjects are the supervisors and administrators of Islamic boarding schools. The results of this study indicate that the planning of the Al-Aziziyah Kapek Gunungsari female Islamic boarding school program for the leadership of the boarding school has compiled a program of female boarding school activities, arranged a schedule, then socialized it to the coaches, administrators, and teachers in order to prepare for the needs in the implementation of the Islamic boarding school program that has been prepared.